2023
DOI: 10.3390/ijms24021096
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab Plus Axitinib for Metastatic Papillary and Chromophobe Renal Cell Carcinoma: NEMESIA (Non Clear MEtaStatic Renal Cell Carcinoma Pembrolizumab Axitinib) Study, a Subgroup Analysis of I-RARE Observational Study (Meet-URO 23a)

Abstract: Non-clear cell renal cell carcinoma (nccRCC) represents a heterogeneous histological group which is 20–25% of those with renal cell carcinoma (RCC). Patients with nccRCC have limited therapeutic options due to their exclusion from phase III randomized trials. The aim of the present study was to investigate the effectiveness and tolerability of pembrolizumabaxitinib combination in chromophobe and papillary metastatic RCC (mRCC) patients enrolled in the I-RARE (Italian Registry on rAre genitor-uRinary nEoplasms)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In our findings, patients who were treated with a first-line immunotherapy combination had a PFS of 12.7 months and an ORR of 42.4%. These results are in line with those reported in the prospective trials described above but, more importantly, are similar to those recently reported in two real-world experiences [25,45]. Furthermore, we can also report that patients who received immunotherapy in their history achieved longer OS than those who did not.…”
Section: Discussionsupporting
confidence: 92%
“…In our findings, patients who were treated with a first-line immunotherapy combination had a PFS of 12.7 months and an ORR of 42.4%. These results are in line with those reported in the prospective trials described above but, more importantly, are similar to those recently reported in two real-world experiences [25,45]. Furthermore, we can also report that patients who received immunotherapy in their history achieved longer OS than those who did not.…”
Section: Discussionsupporting
confidence: 92%
“…90 91 Similarly, the combination of pembrolizumab plus axitinib has shown activity in pRCC and chRCC, demonstrating a DCR of 78.1%, ORR 43.7% (9/11 in pRCC, 5/13 in chRCC) with median PFS 10.8 months. 92 These results are promising for the efficacy of TKI and ICI combinations in the future.…”
Section: Combination Tki Plus Ici Therapymentioning
confidence: 89%
“…Preliminary findings from the phase II KEYNOTE‐B61 trial were presented at the 2022 European Society of Medical Oncology meeting, including 51 patients with pRCC, 15 with chRCC, 7 with unclassified nccRCC, 5 with tRCC and 4 “others.” At median follow‐up of 8.2 months and across IMDC risk‐categories, this regimen yielded an ORR of 47.6% (3.7% CR, 43.9% PR) and DCR(including SD) of 79.3%, with 6‐month PFS and OS rates of 72.3% and 87.8%, respectively 91 . Similarly, the combination of pembrolizumab plus axitinib has shown activity in pRCC and chRCC, demonstrating a DCR of 78.1%, ORR 43.7% (9/11 in pRCC, 5/13 in chRCC) with median PFS 10.8 months 92 . These results are promising for the efficacy of TKI and ICI combinations in the future.…”
Section: Treatmentmentioning
confidence: 99%
“…ICI-based combinations are nowadays the preferred treatment option for advanced RCC, with rates of objective responses ranging from 39% to 71% and rates of complete responses ranging from 6% to 16% [3‒6, 13, 14]. Moreover, a correlation between depth of response and survival outcomes was observed in large randomized phase 3 trials [4, 15].…”
Section: Discussionmentioning
confidence: 99%